Location Decisions of Foreign Banks and Competitive Advantage - Claessens, Stijn (World Bank, Washington, DC, 2012)
While institutional differences have been found to affect country growth patterns, much has remained unexplained, including how economic actors "overcome" institutional weaknesses and how internationalization helps or hinders development. Banking is an institutionally-intensive activity and the location decision of foreign banks provides a good test of how institutional differences are dealt with and how they may affect economic choices. Specifically, the authors examine whether banks seek out those markets where institutional familiarity provides them with a competitive advantage over other foreign competitor banks. Using bilateral data on banking sector foreign direct investment in all developing countries and controlling for other factors, they find that competitive advantage is an important factor in driving foreign banks' location decisions. The findings suggest that high institutional quality is not necessarily a prerequisite to attract foreign direct investment in banking and that there are specific benefits, as well as risks, to international financial integration between developing countries.